Legislação ambiental e os usos da água pelos produtores de leite na Comunidade Sobradinho - Uberlândia-MG - Melo, Marília Christina Arantes (2017)
There’s a socio-territorial (re) order in process, from which tensions can’t be disregarded. In this context, the river basin is the territorial unit for the implementation of water resources management in Brazil. The studies take place in a river basin of the Brazilian Cerrado, more specifically in the Community of Sobradinho, in the city of Uberlândia (MG). In our studies we use the territory category, since it helps us understand the relationships that involve social and physical processes, considering that where there is relationship, there is power, conflicts, tensions and contradictions. In this (re) ordering, the State makes use of the legal apparatus to indoctrinate social practices and in this territory we are studying, inhabit subjects that have territorial ties nourished by the community. In understanding territorialities, we have seen how these bonds are established by the parties. With the territory category, we discuss the specificities and the territorial ties. Thus, the use of the territory category is justified by the territorialities of the farmers that were constituted throughout their historical and cultural development, such as the social relations and the territorial ties that are being built in the place. We can consider in this process the various uses of the territory and their meanings. In these uses of the territory we seek to understand the transformations that occurred through the environmental legislation and the uses of water by the families involved with the milk activity in the Quilombo Stream Hydrographic Basin. In the area of study, the territory is a perceived achievement along the experience that each subject realizes (re) formulates and / or (re) organizes in the lived space. It is necessary to consider that the territory is also felt, since it has always been a reference of belonging to its residents. According to the current environmental legislation, all farmers must also be "producers" of water. We call "farmers" water all farmers who comply with environmental legislation, as well as follow land use and management measures, so that they conserve natural resources, highlighting water as a fundamental asset to guarantee life, according to the Program Water Producers of the National Water Agency. In the implementation of the laws there are tensions and disagreements in place, of which the thesis deals. Thus, the subjects of the research were studied from the perspective of meeting the norms through the path of mutuality, reciprocity, loan, exchange. And, in that sense, another fundamental category is the place, because it makes possible to think the community, which is common in the area of study. In their demands trigger peasant practices, old, indicating a peasantry that metamorphosed in other situations of life. Among the knowledge and skills involved, there is also ethics and religious morality. We consider the dialectic between the new and the old and what the relationship promotes in terms of life strategy. Strategies and outputs that often are not those that contemplate the legislation. But, they solve very specific situations for these farmers. These situations bring numerous disagreements and generate tensions that will be discussed throughout the chapters.